Lived experiences of night work in nurses: A phenomenological study - Khademi, mozhgan; alhani, fatemeh; Goli Kenari, maryam (Advances in Nursing & Midwifery, 2012)
Abstract Background and aim Night work creates widespread and complicated problems for nurses that effect on quality of care, nurses’ and clients’ health, Safety and ability of work force retention. The aim of this study was to discover nature and structure of nursing experiences about night work